An evaluation of DNA damage in human lymphocytes and sperm exposed to methyl methanesulfonate involving the regulation pathways associated with apoptosis. (October 2017) - Habas, Khaled; Najafzadeh, Mojgan; Baumgartner, Adolf; Brinkworth, Martin H.; Anderson, Diana
Abstract: Exposure to DNA-damaging agents produces a range of stress-related responses. These change the expression of genes leading to mutations that cause cell cycle arrest, induction of apoptosis and cancer. We have examined the contribution of haploid and diploid DNA damage and genes involved in the regulation of the apoptotic process associated with exposure, The Comet assay was used to detect DNA damage and quantitative RT-PCR analysis (qPCR) to detect gene expression changes in lymphocytes and sperm in response to methyl methanesulfonate. In the Comet assay, cells were administered 0–1.2 mM of MMS at 37 °C for 30 min for lymphocytes and 32 °C for 60 min for sperm to obtain optimal survival for both cell types. In the Comet assay a significant increase in Olive tail moment (OTM) and % tail DNA indicated DNA damage at increasing concentrations compared to the control group. In the qPCR study, cells were treated for 4 h, and RNA was isolated at the end of the treatment. qPCR analysis of genes associated with DNA stress responses showed that TP53 and CDKN1A are upregulated, while BCL2 is downregulated compared with the control. Thus, MMS caused DNA damage in lymphocytes at increasing concentrations, but appeared not to have the same effect in sperm at the low concentrations. These results indicate that exposure to MMS increased DNA damage and triggered the apoptotic response by activating TP53, CDKN1A and BCL2 . These findings of the processing of DNA damage in human lymphocytes and sperm should be taken into account when genotoxic alterations in both cell types are produced when monitoring human exposure. Highlights: Human Lymphocytes and sperm cells exposure to MMS produced significant DNA damage and apoptosis. DNA damage following MMS exposure in vitro was evaluated in the Comet assay in both cell types. DNA damage and apoptosis resulted in increased P53 and decreased CDKN1A and BCl-2. Human sperm were more susceptible to DNA damage than lymphocytes.